Educación Abierta Y Continua Para La Formación De Emprendedores Rurales En Ecoturismo Y Desarrollo Sustentable Del Cantón Cumandá- Chimborazo. PROYECTO DE EDUCACIÓN DE ADULTOS - Monserrate Manobanda, Isabel (2015)
The present research work aims to vital establish and increase the training of entrepreneurs rural ecotourism and sustainable development, having the knowledge of reality, creative, practical, capable of generating jobs, with the aim of creating profiles of entrepreneurs and thus enable the design of educational objectives, creating professional competencies to establish hubs of learning of the rural entrepreneur in ecotourism and sustainable development for the benefit of the community. Identify the importance of analysis of ecotourism and its sustainable development in which the community of Cumandá is and establish the need for increased as proposed, according to the methodology and scientific bases for establishing such information accessible in this way reach the proposed objectives, so the idea of research is set to be held in this investigative project also a brief description of ecotourism and its involvement depending on the type of problem that has developed in this community.